Carbon Dioxide Enrichment Effects on Growth and Physiological Attributes of Oil Palm Seedlings - Ibrahim, Mohd Hafiz (2008)
The demand for Elaeis guineensis Jacq. (oil palm) seedlings keeps increasing by the years due to an increased need in replanting of palms over the age of 25 years. In 2006, about 89% of oil palm area was under mature palms. However, replanting of oil palm is faced with major constraint due to the long period of seedling establishment, which usually takes about 11 – 12 month in nursery before seedlings can be transplanted out to the field. Subsequently, cost of seedling establishment and nursery management remains high and economic pay back slows due to relatively late bearing. Development of a new technique that can enhance seedling growth and reduce nursery period would mean generation of high income to oil palm propagators and growers. One possible way to enhance seedling growth and development is by CO2 enrichment although responses to CO2 enrichment can be species dependent. Therefore, the main objective of the study was to examine the effects of CO2 enrichment on the growth and physiological responses of three progenies of oil palm seedlings. It was hypothesized that CO2-enriched palms would increase their relative growth rate (RGR) and total biomass through the enhanced of water use efficiency (WUE) and net photosynthesis (A). In accomplishing the research, two experiments were carried out bearing the following specific objectives, namely: 1) to investigate the effects of different CO2 concentrations on seedling growth, leaf gas exchange and macronutrients status of three oil palm progenies; and; 2) to examine the effects of different durations of CO2 enrichment on growth of oil palm seedlings. In experiment one, three tenera progenies of oil palm seedlings, Deli Urt, Deli Yangambi and Deli AVROS were exposed to three levels of CO2 enrichment viz ambient CO2 (control) twice ambient carbon CO2 (800 μmol/mol) and thrice ambient CO2 (1200 μmol/mol). The enrichment treatments were carried out continuously for six days per week between 0800 to 1000am for 15 weeks. Treatments were arranged in a Split Plot RCBD design replicated three times. Each treatment consisted of 10 palms with CO2 levels as the main plot and progenies, as the subplot. Results showed there were no interaction between CO2 and progenies enrichment neither were there preference for CO2 by the progenies observed. However, CO2 imposed (p≤0.05) a very marked effect on the growth and the leaf gas exchange parameters although all the variables measured did not differ significantly when palms were exposed to 800 and 1200 μmol/mol of CO2. Exposing seedlings to higher (800 μmol/mol) CO2 concentration resulted in higher total biomass, net assimilation rate (NAR), RGR, plant height, frond number, basal diameter and total leaf area compared to the controlled seedlings. As further increase in CO2 concentration (1200 μmol/mol) occurred, seedlings become acclimatized to increased quantum efficiency of PSII (Fv/Fm). However total chlorophyll content and stomata density (pores/mm2) reduced. Higher CO2 concentration than ambient affected leaf gas exchange. Upon enrichment, net photosynthesis (A) and WUE increased, but there was reduction in stomata conductance (gs) and evapotranspiration rate (E). Increase in WUE under increased CO2 concentration implied that plant could utilize water per unit carbohydrate produced especially when undergoing stress. Seedlings treated with high CO2 increased their apparent quantum yield (α) and A max but light compensation point was reduced. Nutrient analysis from leaves showed that oil palm seedling treated with high CO2 are deficient in nutrients compared to control. Total N, P, K, Ca and Mg were significantly reduced (p≤0.05) in all the CO2 treatments but total carbon and C:N ratio increased. Enrichment with 800 μmol/mol CO2 was most efficient in enhancing growth and photosynthetic traits of oil palm seedlings although there was no significant difference between the three progenies. Result suggested, that enrichment with CO2 could improve growth of oil palm seedling. The study also proved that a two-hour straight fertilization with CO2 was able to enhance the growth of oil palm seedlings by increasing the photosynthetic rate, WUE and apparent quantum yield (α). In the second experiment, seedlings were exposed to different duration of CO2 enrichment viz: two hours (0800 – 1000; Control), three hours (0800 – 1100), and four hours (0800 – 1200) at 800 μmol/mol CO2. The treatments were arranged in Randomized Complete Block Design (RCBD) replicated three times, and each treatment consisted of 12 palms. There was no significant difference in frond number, total chlorophyll contents, plant height, basal diameter, leaf area, total plant biomass, leaf area ratio, leaf weight ratio, shoot to root ratio, NAR and RGR when palms were exposed to different duration of CO2 enrichment. The result suggested that enrichment for two hours was efficient to enhance growth of oil palm seedling and that further increase in exposure time to CO2 enrichment did not help to further increase the growth. The results showed that CO2 at 800 μmol/mol with 2-hours of exposure was effective in increasing plant growth by increasing total biomass, RGR and NAR by 112, 18 and 70% respectively thus reducing the time for plants to be maintained in the nursery by 4 months.